Childhood MMR Vaccination and the Incidence Rate of Measles Infection - Ahmed Ejaz, Ahmed Ammad, Umar Arif, Saleha Islam, Rabia Islam, Abdullah Islam (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The efficacy of the measles, mumps, and rubella (MMR) immunization in children against subsequent measles diagnoses was the focus of this research. Method: After the ethical approval from institution review board, this crossectional study was conducted at Indus hospital lahore. In this study, MMR vaccination data was collected from all the government vaccination centers from 1st January 2019 till 1st January 2023. Individuals’ month and year of enrollment, gender, date of birth, and county level domicile were all included in the comprehensive eligibility data. Each person’s diagnostic status was recorded in great detail in their claims file. Those who received just one dose of the MMR vaccination were included as part of the vaccinated group, whereas those who did not get any kind of vaccine containing measles were excluded from the research. Participants who had previously received more than one dose of MMR or any other measles-containing vaccine were not included in this analysis. Results: There were a total of 2000 people in the MMR-vaccinated cohort, accounting for 1543 person-years of data, and a total of 5000 people in the unvaccinated cohort, accounting for 3423 person-years of data. The male-to-female ratio in the MMR-vaccinated group was 0.97, while it was 1.13 in the unvaccinated group. 7% children in the MMR vaccinated group were diagnosed with measles, while 25% children in the unvaccinated group was diagnosed with measles. Conclusion: The prevalence of measles infections in children has been drastically decreased due to widespread MMR immunization. Keywords: MMR, measles, childhood, immunization